The Effect Of The Rockmass Properties And Groundwater Inflow Related To Performance Of Tunnel Boring Machine (Tbm) At Pahang Selangor Raw Water Transfer Tunnel Project (Psrwt - Rahim, Afikah (2015)
Groundwater inflow into tunnels can constitute a potential hazard and an important factor influencing the performance of tunnel excavation. In this research, the results on analyses of localised jointing system are presented to study the link of groundwater inflow and the joint orientations along the 2000 meters of TBM-1 site, Karak in conjunction to the construction of Pahang Selangor Raw Water Transfer Tunnel project (PSRWT). The geology along the tunnel route is predominantly the Main Range granite batholith with a lesser extent of meta-sedimentary rocks of the Karak Formation. Structurally, TBM-1 is dominated by joints orientated at N-S, NW-SE and NE-SW direction. Faults that cross-cut the intrusive Main Range Granite rocks trending faults formed the most prominent structures in the vicinity of the Karak. Potential leakage places are identified of three main types of joints orientations; the most permeable place is parallel along the main lineament orientation, followed by perpendicular to 90 degrees to the tunnel drive direction, 45 degrees to the lineament line or combinations of both joints and crossing some of voids which creating pocket water zones. At least three sets of prominent topographic lineaments correspond to fault-zones permeability related. Based on the stereographical projection and rosette diagram analysis, the dominant orientations of joints seem to have occurred at the intersection of 3 cross-cutting trends. They are the Kuala Lumpur – Bukit Tinggi trend, N-S trend and NE-SW trend, which corresponds to the NW-SE Bukit Tinggi and Kuala Lumpur Fault Zones, the N-S faults and the NE-SW faults, respectively. Results from the mechanical tests, Uniaxial Compressional Strength Test, Brazillian Tensile Test, Triaxial by comparing dry and wet condition of rockmass showed that the value of rockmass strength were lessened into half. Parameter values that obtained from the mechanical tests were used in the finite element method analysis showed that rockmass with poor grade and in wet condition have higher potential to deform compared to dry and higher grade rock.